Chinese patients with hereditary spastic paraplegias (HSPs): a protocol for a hospital-based cohort study. Issue 1 (11th January 2022) - Qiu, Yu-Sen; Zeng, Yi-Heng; Yuan, Ru-Ying; Ye, Zhi-Xian; Bi, Jin; Lin, Xiao-Hong; Chen, Yi-Jun; Wang, Meng-Wen; Liu, Ying; Yao, Shao-Bo; Chen, Yi-Kun; Jiang, Jun-Yi; et al.
Abstract : Introduction: Hereditary spastic paraplegias (HSPs) are uncommon but not rare neurodegenerative diseases. More than 100 pathogenic genes and loci related to spastic paraplegia symptoms have been reported. HSPs have the same core clinical features, including progressive spasticity in the lower limbs, though HSPs are heterogeneous (eg, clinical signs, MRI features, gene mutation). The age of onset varies greatly, from infant to adulthood. In addition, the slow and variable rates of disease progression in patients with HSP represent a substantial challenge for informative assessment of therapeutic efficacy. To address this, we are undertaking a prospective cohort study to investigate genetic–clinical characteristics, find surrogates for monitoring disease progress and identify clinical readouts for treatment. Methods and analysis: In this case-control cohort study, we will enrol 200 patients with HSP and 200 healthy individuals in parallel. Participants will be continuously assessed for 3 years at 12-month intervals. Six aspects, including clinical signs, genetic spectrum, cognitive competence, MRI features, potential biochemical indicators and nerve electrophysiological factors, will be assessed in detail. This study will observe clinical manifestations and disease severity based on different molecular mechanisms, including oxidative stress, cholesterol metabolism and microtubule dynamics, all of which have been proposed as potential treatment targets or modalities. The analysis will also assess disease progression in different types of HSPs and cellular pathways with a longitudinal study using t tests and χ 2 tests. Ethics and dissemination: The study was granted ethics committee approval by the first affiliated hospital of Fujian Medical University (MRCTA, ECFAH of FMU (2019)194) in 2019. Findings will be disseminated via presentations and peer-reviewed publications. Dissemination will target different audiences, including national stakeholders, researchers from different disciplines and the general public. Trial registration number: NCT04006418 .